2003
DOI: 10.1523/jneurosci.23-11-04689.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Human Intraparietal and Frontal Cortex for Attending, Looking, and Pointing

Abstract: We studied the functional organization of human posterior parietal and frontal cortex using functional magnetic resonance imaging (fMRI) to map preparatory signals for attending, looking, and pointing to a peripheral visual location. The human frontal eye field and two separate regions in the intraparietal sulcus were similarly recruited in all conditions, suggesting an attentional role that generalizes across response effectors. However, the preparation of a pointing movement selectively activated a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

68
431
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 568 publications
(506 citation statements)
references
References 81 publications
68
431
4
3
Order By: Relevance
“…Thus, superior parietal cortex has been shown to be involved in sensory-motor integration (Andersen, Snyder, Bradley, & Xing, 1997; Iacoboni, Woods, & Mazziotta, 1998;Tanabe, Kato, Miyauchi, Hayashi, & Yanagida, 2005) and motor attention (i.e., covert preparation of an upcoming movement, switching intended movements, hand-eye coordination) (Astafiev et al, 2003;Battaglia-Mayer & Caminiti, 2002;Rushworth, Johansen- Berg, Gobel, & Devlin, 2003). Consistent with this idea, large RS was also found in premotor cortex (BA 6), a region that is important for planning movements and that receives strong inputs from the superior parietal lobule (Schubotz & von Cramon, 2003;Wise, Boussaoud, Johnson, & Caminiti, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, superior parietal cortex has been shown to be involved in sensory-motor integration (Andersen, Snyder, Bradley, & Xing, 1997; Iacoboni, Woods, & Mazziotta, 1998;Tanabe, Kato, Miyauchi, Hayashi, & Yanagida, 2005) and motor attention (i.e., covert preparation of an upcoming movement, switching intended movements, hand-eye coordination) (Astafiev et al, 2003;Battaglia-Mayer & Caminiti, 2002;Rushworth, Johansen- Berg, Gobel, & Devlin, 2003). Consistent with this idea, large RS was also found in premotor cortex (BA 6), a region that is important for planning movements and that receives strong inputs from the superior parietal lobule (Schubotz & von Cramon, 2003;Wise, Boussaoud, Johnson, & Caminiti, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This difference between the two task conditions was not observed after smokers smoked a cigarette, nor was it exhibited by nonsmokers in either test. Literature regarding selective attention indicates that activity of the FEF (including the adjacent regions around the precentral sulcus) mediates shifts of attention and discrimination between targets and distracters (Astafiev et al, 2003;Hopfinger et al, 2000). For example, FEF neurons in monkeys are activated during discrimination between targets and distracters (Bichot and Schall, 1999;Thompson and Bichot, 2005); and the FEF is activated by distracters while human subjects perform an oddball task (Bledowski et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There was condition-dependent modulation of the aIPS such that the grasping condition produced the most activation, followed in descending order by imagined grasping, visual discrimination, and color discrimination, which produced the least activation. The aIPS in humans might also be involved in preparatory activity for multieffector action [28]; the investigators observed activation in the aIPS when a lateralized visual target was covertly attended, fixated with a saccade, or pointed to with a finger ([29] see also Macaluso et al [25]). Interestingly, the aIPS was activated in tasks that involved a delay period between presentations of task-associated visual and/or tactile information, which suggests a role in sensorimotor transformation.…”
Section: Parietal Cortex and Attentionmentioning
confidence: 99%
“…The question of whether or not the human aIPS is homologous to monkey AIP, which is involved in visually guided grasping, is still very much open [27,28,30]. In addition to the disagreement regarding the functional nature of aIPS, there is also variance in the peak Talairach coordinates listed for aIPS in each of these papers.…”
Section: Parietal Cortex and Attentionmentioning
confidence: 99%
See 1 more Smart Citation